A greener prescription: the power of natural organic materials in healthcare - Paulin, João V. [UNESP] (Royal Society of Chemistry (RSC), 2024)
Natural organic materials might offer a sustainable solution at the crossroads of technological progress and environmental degradation. Natural organic materials (NM), which are biodegradable, biocompatible, renewable, and electroactive, offer a sustainable solution to the environmental impact of technological progress. This perspective emphasizes NM's potential to reduce environmental impact and create sustainable solutions for medical devices and disposable products. Nonetheless, challenges remain in scaling up production and addressing durability. Integrating natural systems into technological processes can help achieve a more eco-friendly and balanced future.